"Človek v pragozdu" pri Dušanu Pirjevcu in Vitomilu Zupanu - Kos, Matevž (Primerjalna književnost, 2017)
The paper analyses the phrase "man in the primeval forest" as employed by Dušan Pirjevec, a Slovenian literary critic, and the similar phrase "expedition into the jungle" as used by Vitomil Zupan, a Slovenian writer. The former is encountered in Pirjevec's posthumously published diary ("Diary and Remembrances", 1986) and the latter in Zupan's novel Minuet for Guitar (1975). The texts were written roughly at the same time, that is, in the mid-1970s. Both authors had joined the Partisans during World War II, an experience which profoundly affected their post-war intellectual and creative careers. The diary of Pirjevec is a philosophical (self)reflection on the Slovenian Partisan movement and the Communist revolution. It is significantly influenced by M. Heidegger's idea of the "ontological difference", an association which enables Pirjevec to reflect on revolution in the larger context of European nihilism, planetary technology and the will to power. Zupan's writing, on the other hand, is based on a vitalism largely conceived as a plea for consistent individualism. The paper highlights the distinctive features of the two works in terms of both content and form, additionally comparing Zupan's novel with other examples of his fiction. In outlining the major similarities and differences between Pirjevec and Zupan, the conclusion partly draws on the semantic nuances of the two phrases, which are a key to understanding the two authors' oeuvres.
Keywords: diary; dnevnik; druga svetovna vojna; ontological difference; ontološka diferenca; Pirjevec, Dušan, 1921-1977; revolucija; revolution; Slovene literature; slovenska književnost; vojni roman; war novel; World War II; Zupan, Vitomil, 1914-1987